Durable high-rate capability Na0.44MnO2 cathode material for sodium-ion batteries. (September 2016) - He, Xin; Wang, Jun; Qiu, Bao; Paillard, Elie; Ma, Chuze; Cao, Xia; Liu, Haodong; Stan, Marian Cristian; Liu, Haidong; Gallash, Tobias; Meng, Y. Shirley; Li, Jie
Abstract: Monocrystalline orthorhombic Na0.44 MnO2 nanoplate as a potential cathode material for sodium-ion batteries has been synthesized by a template-assisted sol-gel method. It exhibits high crystallinity, pure phase and homogeneous size distribution. During the synthesis, acidic and reductive conditions are applied to limit the production of unfavorable Birnessite phase in the precursor, and colloidal polystyrene is included to avoid morphology collapse during the gel formation and particle elongation in one direction. The decompositions of polystyrene and citric acid during high temperature firing offer a reductive carbothermal condition which can suppress the formation of unidimensional particles, and limit particle growth along the [001] direction. As a consequence, the material delivers 96 mAh g −1 discharge capacity at 10 C (86% of 0.1 C capacity) and maintains 97.8% capacity after 100 cycles at 0.5 C. Such superior rate capability and cycling stability of this material are among the best to date, suggesting its great interest in practical applications. Graphical abstract: The Na0.44 MnO2 materials were achieved with a template assisted sol-gel method. The prepared materials showed high crystallinity, pure phase and homogeneous size distribution. The materials exhibited superior electrochemical performance in both rate capability and cycling stability due to the limited crystal growth along [001] direction. Highlights: A template assisted sol-gel method is used to prepare Na0.44 MnO2 nanoplates. The Na0.44 MnO2 nanoplates with high purity show good electrochemical performance. The nanoplates with limited crystal growth along [001] facilitate Na-ion diffusion.